Steel decarbonization in China – a top-down optimization model for exploring the first steps. (15th January 2023) - Li, Zhenxi; Andersson, Fredrik N.G.; Nilsson, Lars J.; Åhman, Max
Abstract: The steel industry is a major contributor to emissions of CO2 and key air pollutants. Reducing air pollution has since long been a policy priority in China. Reducing CO2 emissions has more recently also become a key priority partially manifested through the signing of the Paris Agreement in 2015. Although there are often synergies between reducing CO2 emissions and air pollution, it may have implications for the geographical location if one is prioritized over the other, with subsequent effects on local economies and overall policy efficiency. Therefore, we build a top-down optimization model to assess the provincial allocation of steel production, air pollution impact and the cost for meeting the target of peaking CO2 emissions in 2025 and reducing them by 30% in 2030. This short-term reduction target can be regarded as the first steps for China's steel industry to meet the national net zero target and the Pairs agreement. We analyze a scenario to minimize air pollution impact and compare this with a scenario to minimize CO2 mitigation costs. The results show that it is possible to peak CO2 emissions in 2025 and reduce them by 30% in 2030 but the resulting scrap demand requires increased quality scrap collection or imports. The total cost for different scenarios is similar but optimizing on abatement cost leads to lower cumulative CO2 emissions 2021–2030 compared to optimizing on pollution impact. If reducing pollution impact is the main objective, it leads to 22–26% lower pollution impact than when optimizing on abatement costs, and less primary production in densely populated areas. This implies that policy must handle trade-offs between cost optimal mitigation and pollution impact, as well as effects on local economies. Policy must also balance the accelerated introduction of Electric Arc Furnaces while simultaneously reducing overcapacity in primary production. Highlights: Chinese steel industry can peak emissions in 2025 and reduce them by 30% in 2030. Scrap availability is the main constraint for reducing emissions by 30% in 2030. The choice of strategy affects where future production will be located. Increasing shares of EAF and reducing overcapacity should be balanced. 122 Mt BF-BOF capacity should be phased-out from 2020 to 2030.